2018
DOI: 10.3389/fmicb.2018.02661
|View full text |Cite
|
Sign up to set email alerts
|

Post-translational Modification Control of HBV Biological Processes

Abstract: Hepatitis B virus infection remains a global healthy issue that needs to be urgently solved. Novel strategies for anti-viral therapy are based on exploring the effective diagnostic markers and therapeutic targets of diseases caused by hepatitis B virus (HBV) infection. It is well-established that not only viral proteins themselves but also key factors from the host control the biological processes associated with HBV, including replication, transcription, packaging, and secretion. Protein post-translational mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 118 publications
1
21
0
Order By: Relevance
“…Chronic infection with HBV has been associated with several liver diseases including hepatitis, cirrhosis, and hepatocellular carcinoma (HCC) [16]. HBx, a 16.5-kDa regulatory protein, is one of the main components of HBV.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic infection with HBV has been associated with several liver diseases including hepatitis, cirrhosis, and hepatocellular carcinoma (HCC) [16]. HBx, a 16.5-kDa regulatory protein, is one of the main components of HBV.…”
Section: Discussionmentioning
confidence: 99%
“…Since ERGIC-53 acts as a high mannose-specific lectin, we next focused on the HBV-specific N-glycans. A number of studies have shown that HBV release requires sugar moieties linked to the N-glycan acceptor N146 of the envelope proteins [11][12][13][14][15][16]. To ascertain the importance of the N146-linked glycans in our experimental settings, we disabled N-glycosylation by creating an asparagine-to-aspartic acid substitution in the HBV envelope expression vector (Env.N146D).…”
Section: Blocking N146-linked Glycosylation Inhibits Hbv Egress Withomentioning
confidence: 99%
“…Within the ER, all three envelope proteins acquire N-linked glycans attached to an asparagine residue (N146) located within a hydrophilic, ER-luminally disposed loop of the S domain. Intriguingly, N-linked glycosylation is essential for the outcome of an HBV infection, as an inhibition of this modification blocks virion egress [11][12][13][14][15][16]. Its significance is substantiated by the strict conservation of N146-linked N-glycosylation in all eight HBV genotypes [17] and even in related hepadnavirus family members, like the woolly monkey hepatitis B virus [18] and the woodchuck hepatitis B virus [19].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, phosphorylation at Ser44, Thr67, Ser141, and Thr142 was detected by MS analysis, but importance of these modifications awaits further studies (Lubyova et al, 2017). stands out as it contains three SP (serine/proline) recognition sequences and CTD was shown to be essential for pgRNA encapsidation, viral DNA synthesis, subcellular localization and virion secretion (Diab et al, 2018;Liu et al, 2015;Yang, 2018).…”
Section: Hbc and Phosphorylationmentioning
confidence: 99%
“…PTMs are among the first events employed by eukaryotic cells to react to infection (Ribet and Cossart, 2010). PTMs, particularly phosphorylation, acetylation, ubiquitination, SUMOylation, or NEDDylation were shown to play important role in both restricting and supporting of HBV replication (Kong et al, 2019;Yang, 2018). The focus of this review are posttranslational modifications of HBV core/ capsid protein, particularly C-terminal serine phosphorylation, ubiquitination and arginine methylation, and their role in core protein function, subcellular trafficking and ability to assemble nucleocapsid.…”
Section: Introductionmentioning
confidence: 99%